High-Resolution Imaging of Patients with Bietti Crystalline Dystrophy with CYP4V2 Mutation. (3rd September 2014) - Gocho, Kiyoko; Kameya, Shuhei; Akeo, Keiichiro; Kikuchi, Sachiko; Usui, Ayumi; Yamaki, Kunihiko; Hayashi, Takaaki; Tsuneoka, Hiroshi; Mizota, Atsushi; Takahashi, Hiroshi
Abstract : The purpose of this study was to determine the retinal morphology of eyes with Bietti crystalline dystrophy (BCD) associated with a CYP4V2 mutation using high-resolution imaging techniques. Three subjects with BCD underwent detailed ophthalmic examinations. High-resolution fundus images were obtained with an adaptive optics (AO) fundus camera. A common homozygous mutation was detected in the three patients. Funduscopic examination of the three patients revealed the presence of crystalline deposits in the retina, and all of the crystalline deposits were also detected in the infrared (IR) images. The crystals observed in the IR images were seen as bright reflective plaques located on the RPE layer in the SD-OCT images. The clusters of hyperreflective signals in the AO images corresponded to the crystals in the IR images. High-magnification AO images revealed that the clusters of hyperreflective signals consisted of circular spots that are similar to the signals of cone photoreceptors. Most of these circular spots were detected in healthy areas in the FAF images. There is a possibility that circular spots observed by AO are residual cone photoreceptors located over the crystals.